2018
DOI: 10.1111/auar.12279
|View full text |Cite
|
Sign up to set email alerts
|

Board Composition and Accounting Conservatism: The Role of Business Experts, Support Specialist and Community Influentials

Abstract: In this study, we examine the relationship between accounting conservatism and board composition. We categorise outside directors according to their skills, abilities, connections and knowledge in three different categories: business experts, support specialists and community influentials. We address three main questions: Is the financial and accounting expertise of directors relevant to improving accounting conservatism? Does specialised expertise in the board affect the speed at which news is reflected in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 75 publications
(204 reference statements)
0
11
0
1
Order By: Relevance
“…According to agency theory, the more diversity on the board, the better monitoring and management of the corporation's activities (Hassan and Marimuthu, 2016;Madhani, 2017). According to the resource dependency theory, diverse members bring more resources in terms of skills, expertise, advice, and counselling as well as access to the external market (Enache and Garcia-Meca, 2019;Fakir and Jusoh, 2020). Research showed that diversity in terms of gender, nationality, age, and higher education, improves corporate decision-making quality, especially as related to environmental and social activities, which leads to improving sustainability performance (Chams and Garcia-Blandon, 2019;Rao and Tilt, 2016b).…”
Section: Board Diversitymentioning
confidence: 99%
“…According to agency theory, the more diversity on the board, the better monitoring and management of the corporation's activities (Hassan and Marimuthu, 2016;Madhani, 2017). According to the resource dependency theory, diverse members bring more resources in terms of skills, expertise, advice, and counselling as well as access to the external market (Enache and Garcia-Meca, 2019;Fakir and Jusoh, 2020). Research showed that diversity in terms of gender, nationality, age, and higher education, improves corporate decision-making quality, especially as related to environmental and social activities, which leads to improving sustainability performance (Chams and Garcia-Blandon, 2019;Rao and Tilt, 2016b).…”
Section: Board Diversitymentioning
confidence: 99%
“…However, they also do not consider firm officers to be independent. 5 Enache and Garcia-Meca (2018) find that politician directors are negatively associated with conservatism in their U.S. biotech sample, which suggests that independent directors vary in their influence on conservatism. 6 SOX requires public firms to disclose whether their audit committees include financial experts or not.…”
Section: Non-officer Directors and Conditional Conservatismmentioning
confidence: 96%
“…Based on their capacity and expertise, the BoD substantially supervises preparing financial statements. BoD has the authority to determine performance targets, reported figures, and the timing of report submissions (Basu & Liang, 2019;Enache & García-Meca, 2019). In addition, the BoD with financial expertise can apply appropriate accounting standards, including accounting conservatism.…”
Section: Board Expertise and Accounting Conservatismmentioning
confidence: 99%
“…Several studies have examined the relationship between BoD characteristics and accounting conservatism. Nevertheless, previous empirical findings show heterogeneous and inconclusive results (Enache & García-Meca, 2019).…”
Section: Introductionmentioning
confidence: 96%